Bone tissue response to implant surfaces functionalized with phosphate‐containing polymers. Issue 1 (8th October 2012) - Cardoso, Marcio Vivan; Chaudhari, Amol; Yoshida, Yasuhiro; Van, Bart; Naert, Ignace; Duyck, Joke
Abstract Objectives Inorganic polyphosphates are said to stimulate the activity of osteoblast‐like cells in vitro. The purpose of this study was to evaluate in vivo bone regeneration around implants treated with polyphosphoric acid (PPA) and phosphorylated pullulan (PPL). Material and Methods Two types of implants with different surface roughness (R1: Sa ≈ 0.23 μm; R2: Sa ≈ 1.35 μm) were treated with three solutions (distilled water, 10%wt PPA, or 10%wt PPL) prior to implantation in both tibia of twelve female white rabbits. Each animal received six implants randomly positioned according to their surface roughness and treatment: R1 + water; R1 + PPA; R1 + PPL; R2 + water; R2 + PPA; R2 + PPL. Animals were sacrificed after 1 or 4 weeks, and samples were prepared for histological and histomorphometrical analysis. Bone regeneration areas were evaluated for bone‐to‐implant contact (BIC) and bone fraction (BF) in areas 100 and 500 μm remote from the implant surface. Data were statistically analyzed by means of Friedman and Wilcoxon matched‐pair tests (P < 0.05). Results After 1 week, bone tissue was rarely formed in the regeneration areas. After 4 weeks, implants treated with PPA presented higher ratios of BIC (R1 = 52.3 ± 13.1; R2 = 54.6 ± 11.0) than the ones treated with water (R1 = 24.1 ± 15.1; R2 = 32.4 ± 13.0). On the other hand, around the implant surface (100 μm), PPL‐treated implants induced higher BF (R1 = 78.3 ± 34.1; R2 = 71.2 ± 21.8) as compared with the water‐treated ones (R1 = 46.1 ± 22.0; R2 = 49.6 ± 21.0). At 500 μm, however, no statistically significant differences in BF were found among the groups evaluated (P > 0.05). Surface roughness influenced neither BIC nor BF. Conclusions Implant surface treatment with phosphate‐containing polymers may positively influence osseointegration.